Гідратоутворення в Чорному морі - Сокур, О.М. (Інститут геологічних наук НАН України, 2009)
Рассматриваются теоретические разработки и фактические данные, которые могут помочь в решении задач освоения газогидратов шельфа и глубоководной части Черного моря. Переинтерпретация материалов прошлых лет позволила выявить три зоны гидратообразования. Одна из структур — Голубиная, или Альфа, находится в пределах северо-западного шельфа. Разрабатываются дистанционные и прямые методы поисков газогидратных скоплений. In the paper, the theoretical notions and field evidences are considered which can help to solve the tasks of gas hydrate development on the shelf and deep-water part of the Black Sea. Re-interpretation of previous data enables to recognize three zones of gas hydrate formation. One of the structures (Golubinaya, or Alpha) occurs in the margins of the northwestern shelf. The remote and direct methods are developed for search of gas hydrate accumulations.